Do Investment Banks Matter for M&A Returns? - Bao, Jack; Edmans, Alex (Review of Financial Studies, 2011)
We document a significant investment bank fixed effect in the announcement returns of M&A deals. The interquartile range of bank fixed effects is 1.26%, compared with a full-sample average return of 0.72%. The results remain significant after controlling for the component of returns attributable to the acquirer. Our findings suggest that investment banks matter for M&A outcomes, and contrast earlier studies that show no positive link between various measures of advisor quality and M&A returns. Differences in average returns across banks are also persistent over time and predictable from prior performance. Clients do not chase past returns, which may explain why persistence exists in M&A performance while it is absent in mutual funds.